Gender-specific association between the regular use of statins and the risk of irritable bowel syndrome: A population-based prospective cohort study - Zhang, Xiaoying; Liu, Yuyao; Ou, Yanghui; Yang, Man; Yuan, Jinqiu; He, Qiangsheng; Li, Yanfei; Mi, Ningning; Xie, Peng; Li, Wenjing; Wu, Siqin; Qin, Xiwen; et al. (Frontiers in Pharmacology, 2023)
Introduction: In addition to lipid-lowering effects, statins might modulate gut microbiome and alleviate systematic inflammation, which in turn, may have a protective effect against irritable bowel syndrome (IBS). The aim of our study is to evaluate the gender-specific association between statins exposure and the risk of IBS. Method: We undertook a prospective analysis based on the UK Biobank, a large ongoing cohort including 477,293 participants aged 37–73 years. We included participants with information on personal statins use and free of IBS and cancer at baseline. We evaluated gender-specific hazard ratio (HR) and 95% confidence interval (CI) with Cox proportional hazards regression, adjusting for demography, lifestyle factors, comorbidities and statin indications. Result: A total of 438,805 participants (male 206,499, female 232,306) were included in the analysis. Among male participants, regular use of statins was associated with a decreased risk of IBS (HR: 0.77; 95% CI: 0.61–0.97). This association persists across multiple sensitivity and subgroup analyses and did not show clear evidence of variance among the major types of statins. We did not find sufficient evidence of association between statins use and IBS risk in female (HR: 0.98, 95% CI: 0.82–1.16). Conclusion: Our study found that regular use of statins was associated with a decreased risk of IBS in male. Further studies are required to confirm the beneficial effect of statins.